PENGARUH AKUNTANSI MANAJEMEN LINGKUNGAN TERHADAP KINERJA PERUSAHAAN MELALUI INOVASI PRODUK DI PT. BERKAH WAKAF INDONESIA - Ayyub Arfang, Muhammad; Badollahi, Ismail; Sahrullah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of environmental management accounting on company performance through product innovation at PT. Berkah Wakaf Indonesia. Environmental management accounting is a tool that integrates environmental information into financial and operational decision making, which is expected to encourage product innovation and improve company performance. This research uses a quantitative approach with primary data obtained through questionnaires distributed to 53 employees of PT. Berkah Wakaf Indonesia. The analysis method used is Partial Least Square Structural Equation Modeling (PLS-SEM) with the help of SmartPLS 3.0 software. The results of this study indicate that: (1) Environmental management accounting has a positive and significant effect on product innovation, with a path coefficient value of 0.521 and p-value of 0.000; (2) Environmental management accounting does not have a significant effect on company performance, with a p-value of 0.917; (3) Product innovation does not have a significant effect on company performance, with a p-value of 0.067; and (4) Product innovation is unable to mediate the effect of environmental management accounting on company performance, with a p-value of 0.096. These findings suggest that while environmental management accounting successfully drives product innovation, the chain from innovation to company performance has not yet been optimally realized. Companies need to more deeply integrate environmental management accounting information into their strategic decision-making processes and product commercialization strategies.